2018
DOI: 10.1159/000486814
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-Induced MicroRNA-211 Inhibits Interleukin-10 in Macrophages of Rats with Lipopolysaccharide-Induced Acute Respiratory Distress Syndrome

Abstract: Background/Aims: The present study addressed the potential involvement of microRNAs in acute respiratory distress syndrome (ARDS)-related inflammation and elucidates the underlying molecular mechanism. Methods: ARDS rat model was established by lipopolysaccharide, with compromised gas exchange capacity and lung edema. The inflammatory cells from bronchoalveolar lavage fluid (BALF) were profiled with automatic blood cell analyzer. The relative fluorescence intensity of BALF-derived macrophages was analyzed by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Many studies have proven that microRNA can mediate the development of ARDS. For example, NF-κB-induced microRNA-211 inhibits IL-10 in macrophages of rats with LPS-induced ARDS [28] [29 40 28 31]. In the present study, microRNA-155-5p expression was significantly elevated in ARDS patients.…”
Section: Discussionsupporting
confidence: 49%
“…Many studies have proven that microRNA can mediate the development of ARDS. For example, NF-κB-induced microRNA-211 inhibits IL-10 in macrophages of rats with LPS-induced ARDS [28] [29 40 28 31]. In the present study, microRNA-155-5p expression was significantly elevated in ARDS patients.…”
Section: Discussionsupporting
confidence: 49%
“…Depending on different circumstances, macrophages may differentiate into two different phenotypes. M1 macrophages (or classically activated macrophage) are pro-inflammatory macrophages that release IL-1β, TNF-α, IL-6 and other inflammatory factors under the stimulation of IFN-γ or lipopolysaccharide (LPS) through the activation of the STAT1 or NF-κB pathway [7,8]. These inflammatory factors are also important cytokines increased in sepsis during severe inflammatory periods.…”
Section: Introductionmentioning
confidence: 99%
“…AMs, once activated by toll-like receptors (TLRs), serve as the first line of defense against invaders into the lung [ 15 ]. Wang et al reported that the NF-κB pathway aberrantly activated in BALF-derived macrophages aroused ARDS in rats [ 16 ]. Therefore, we supposed that the LPS-induced IL-33 secretion requires activation of the TLR4/NF-κB pathway since NF-κB is the central mediator of inflammation.…”
Section: Discussionmentioning
confidence: 99%